UPAYA PENINGKATAN PEMAHAMAN KONSEP FISIKA SISWA MELALUI PENERAPAN MODEL PEMBELAJARAN SQ3R (SURVEY, QUESTION, READ, RECITE & REVIEW) - HIMSAR SIREGAR SIREGAR (Tazkir : Jurnal Penelitian Ilmu-ilmu Sosial dan Keislaman, 2017)
This study departs from the problem of non-contestual learning material and low students’ performance, most teachers still carry out learning in a monotonous method. Based on the problems this research this research conducted, with the aim of increasing the understanding of students' physics concepts and teacher activities in physics learning using the SQ3R learning model. This research was conducted at SMA N 1 Siabu through classroom action research with two cycles. In the first cycle, some students and teachers were not familiar with the learning conditions of the SQ3R model. In the second cycle, students and teachers have begun to understand the implementation of SQ3R learning, and have shown satisfactory results. It can be seen from the results of observations of teachers and students getting used to putting the learning atmosphere that leads to the SQ3R learning approach. From the test results, it is known that the understanding of students' physics concepts increased from 55.62 to 73.75; an average score is 64.66 which can be categorized as good. Mastery of learning improved from 25% in the first cycle to 67.5% in the second cycle. From the result above, it concluded that SQ3R learning can improve the understanding of students' physics concepts in physics learning in class X SMA N 1 Siabu in the academic year 2010-2011.